2020
DOI: 10.3390/ijms21093227
|View full text |Cite
|
Sign up to set email alerts
|

Highly Expressed FOXF1 Inhibit Non-Small-Cell Lung Cancer Growth via Inducing Tumor Suppressor and G1-Phase Cell-Cycle Arrest

Abstract: Cancer pathogenesis results from genetic alteration-induced high or low transcriptional programs, which become highly dependent on regulators of gene expression. However, their role in progressive regulation of non-small-cell lung cancer (NSCLC) and how these dependencies may offer opportunities for novel therapeutic options remain to be understood. Previously, we identified forkhead box F1 (FOXF1) as a reprogramming mediator which leads to stemnesss when mesenchymal stem cells fuse with lung cancer cells, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…The FOXF1 transcription factor regulates E-cadherin expression downstream of the P53 family members, modulating cancer cell migration and invasion [ 27 ]. In NSCLC, FOXF1 may inhibit cancer growth by inducing tumor suppressor and G1-phase cell-cycle arrest [ 28 ]. In LUAD in our study, downregulation of FOXF1 and positive survival results were observed.…”
Section: Discussionmentioning
confidence: 99%
“…The FOXF1 transcription factor regulates E-cadherin expression downstream of the P53 family members, modulating cancer cell migration and invasion [ 27 ]. In NSCLC, FOXF1 may inhibit cancer growth by inducing tumor suppressor and G1-phase cell-cycle arrest [ 28 ]. In LUAD in our study, downregulation of FOXF1 and positive survival results were observed.…”
Section: Discussionmentioning
confidence: 99%
“…References to the Figure 1 . Kilvaer et al [ 16 ]; Tao et al, 2017 [ 19 ]; Donnem et al, 2008 [ 20 ]; Kilvaer et al, 2018 [ 15 ]; Kilvaer et al, 2015 [ 13 ]; Edlund et al, 2012 [ 21 ]; Saito et al, 2010 [ 22 ]; Wu et al, 2020 [ 23 ]; Mattsson et al, 2015 [ 24 ]; Yokouchi et al, 2015 [ 25 ]; Hellevik et al, 2012 [ 12 ]; Hellevik et al, 2013 [ 9 ]; Grinde et al, 2017 [ 26 ].…”
Section: Figurementioning
confidence: 99%
“…After the intersection of these 181 genes and 998 DEGs, 4 CNV-driven genes are obtained, namely ABR, EFNB3, FOXF1, ZFP3, whose expressions all decreased in the high mRNAsi group, possibly due to the loss of fragments. Reportedly, FOXF1 inhibits the growth of non-small cell lung cancer by activating tumor suppressor p21 [38]. However, its role and molecular mechanism in high stemness cancer cells remain to be further studied.…”
Section: Discussionmentioning
confidence: 99%